2014
DOI: 10.1073/pnas.1420375111
|View full text |Cite
|
Sign up to set email alerts
|

Agonists of growth hormone-releasing hormone stimulate self-renewal of cardiac stem cells and promote their survival

Abstract: The beneficial effects of agonists of growth hormone-releasing hormone receptor (GHRH-R) in heart failure models are associated with an increase in the number of ckit + cardiac stem cells (CSCs). The goal of the present study was to determine the presence of GHRH-R in CSCs, the effect of GHRH-R agonists on their proliferation and survival, and the mechanisms involved. We investigated the expression of GHRH-R in CSCs of different species and the effect of GHRH-R agonists on their cell proliferation and survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 69 publications
4
29
0
Order By: Relevance
“…Following the seminal description by Beltrami et al (16) of clusters of cKit cells in the postnatal mammalian heart, several laboratories, including ours, suggested that cKit marks CPs (16)(17)(18)(19), a finding that led to the clinical testing of these cells for heart repair (20). Recently, a straightforward genetic fate-mapping study showed that a relatively small proportion of murine myocardium is derived from cKit + CPs, leading to the conclusion that the cardiomyogenic capacity of cKit + CPs is functionally insignificant (21).…”
Section: Creert2mentioning
confidence: 81%
“…Following the seminal description by Beltrami et al (16) of clusters of cKit cells in the postnatal mammalian heart, several laboratories, including ours, suggested that cKit marks CPs (16)(17)(18)(19), a finding that led to the clinical testing of these cells for heart repair (20). Recently, a straightforward genetic fate-mapping study showed that a relatively small proportion of murine myocardium is derived from cKit + CPs, leading to the conclusion that the cardiomyogenic capacity of cKit + CPs is functionally insignificant (21).…”
Section: Creert2mentioning
confidence: 81%
“…GHRH has been shown to induce proliferation of pituitary somatotroph cells; the pathway involving cAMP/protein kinase A is important in cells targeted by GHRH (22,23). It was also reported that GHRH(1-29)NH 2 and its agonists can activate mitogen-activated protein kinase (MAPK) in pituitary cells, porcine stem cells (15), and in cell lines overexpressing the GHRH receptor (24,25), whereas GHRH antagonists inhibit cAMP production and inactivate ERK and AKT kinases in cancer cells (26,27). However, the mechanism of GHRH and its agonists on pancreatic β cells has not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothalamic growth hormone-releasing hormone (GHRH) stimulates production and release of GH from the pituitary gland, exerts some of its effects through the GH/IGF axis, and also directly affects extrapituitary cells expressing GHRH receptors by activating these receptors. GHRH receptor(s) have been detected in various tumor cells, stem cells, and other tissues including pancreatic β cells (12)(13)(14)(15)(16). Understanding the action of GHRH on its target cells is important for potential application in the use of synthetic GHRH analogs, with prolonged half-lives, which may provide a promising pharmacologic therapy in various fields.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Foresta et al reported that vardendafil promoted significant mobilization of endothelial progenitor cells in patients [22]. Recently, Hare and colleagues reported that PC of cardiac stem cells with agonists of growth hormone-releasing hormone receptor promoted their proliferation and survival [23]. Besides the direct effect of PDE inhibitors on stem cell survival, overexpression of PKG-I, an important mediator of protection, through adenoviral transduction also increases stem cell survival upon oxygen glucose deprivation as well as cardioprotection against myocardial infarction [24].…”
mentioning
confidence: 99%